Flow injection tyrosinase biosensor for direct determination of acetaminophen in human urine - Frangu, Arbër; Pravcová, Kateřina; Šilarová, Petra; Arbneshi, Tahir; Sýs, Milan (Analytical and bioanalytical chemistry, 2019)
An amperometric biosensor compatible with a flow injection analysis (FIA) for highly selective determination of acetaminophen (APAP) in a sample of human urine was developed. This biosensor is also suitable for use in the routine pharmaceutical practice. To prove this statement, two different commercially available pharmaceutical formulations were analyzed. This nano-(bio)electroanalytical device was made from a commercially available screen-printed carbon electrode covered by a thin layer of non-functionalized graphene (NFG) as amperometric transducer. A biorecognition layer was prepared from mushroom (Agaricus bisporus) tyrosinase (EC 1.14.18.1) cross-linked using glutaraldehyde, where resulting aggregates were covered by Nafion®, a known ion exchange membrane. Owing to the use of tyrosinase and presence of NFG, the developed analytical instrument is able to measure even at potentials of 0 V. Linear ranges differ according to choice of detection potential, namely up to 130 μmol L-1 at 0 V, up to 90 μmol L-1 at -0.1 V, and up to 70 μmol L-1 at -0.15 V. The first mentioned linear range is described by the equation Ip [μA] = 0.236 - 0.1984c [μmol L-1] and correlation coefficient r = 0.9987; this equation was used to quantify the content of APAP in each sample. The limit of detection of APAP was estimated to be 1.1 μmol L-1. A recovery of 96.8% (c = 25 μmol L-1, n = 5 measurements) was calculated. The obtained results show that FIA is a very selective method for APAP determination, being comparable to the chosen reference method of reversed-phase high-performance liquid chromatography.
Keywords: limita detekce; neopioidní analgetika; Monophenol Monooxygenase; Humans; tyrosinasa; Limit of Detection; lidé; Urinalysis; design vybavení; Analgesics, Non-Narcotic; biosenzitivní techniky; průtoková injekční analýza; Equipment Design; Flow Injection Analysis; analýza moči; Biosensing Techniques; Agaricus; paracetamol; Acetaminophen